The Role of Systemic Inflammation in Psychiatric Disorders Development in Children: Literature Review - Daria A. Emelina; Ilya V. Kravchenko; Igor V. Makarov; Rauf F. Gasanov; Ekaterina S. Prokhorenko ("Paediatrician" Publishers LLC, 2024)
There has been significant increase in mental disorders prevalence in pediatric population around the world. Increasing incidence of autism, intellectual incapacity, hyperkinetic disorders, and schizophrenia gives causes for specific concern. Clarifying mental disorders' etiology and pathogenesis is the priority of researchers. The role of systemic inflammation in psychiatric disorders development currently remains the least studied. However, it can already be stated that generalized peripheral inflammation is the important factor associated with the development of mental disorders both in adults and children. This review presents latest data, as well as an authors' assessment of systemic inflammation role in the most common mental disorders development in children. Comparative analysis of acute and chronic systemic inflammation manifestations has been performed. The major pathogenetic mechanisms of "systemic damage" in mental disorders have been identified.